Physical demands during the game and compensatory training sessions (MD + 1) in elite football players using global positioning system device - Calderón-Pellegrino, G.; Gallardo, L.; Garcia-Unanue, J.; Felipe, J. L.; Hernandez-Martin, A.; Paredes-Hernàndez, V.; Sánchez-Sánchez, J. (Sensors, 2022)
The aims of this study were to analyze the differences of physical demands of non-starter players regarding the playing time during the competition and to evaluate the physical demands of the compensatory training (MD + 1C) for substitute players in elite football. The match statistics and MD + 1C of substitute players from a professional Spanish LaLiga football club were analyzed using a 10-Hz global positioning system (GPS) Apex GPS system device, which has been validated as a reliable and valid method to analyze performance in team sports, during all games of the 2016/2017, 2017/2018 and 2018/2019 seasons. The starting players showed both lower total distances covered and high-intensity actions compared to the substitutes. Regarding the minutes played by the substitutes, greater physical performance was found for the players with fewer minutes (5-15 min). Furthermore, no differences were found between first and second divisions regarding physical performance of substitutes (p > 0.05). This study highlights the importance of individualizing the workload of training sessions for substitutes and starters. Furthermore, the complementary session should be individualized according to the minutes played by the substitutes. These players are potentially under-loaded compared to starters, especially in terms of high-intensity actions, therefore additional session-specific training for each substitute would be useful to reach the optimal training load according to the minutes played during the game.